IMPLIKASI PRODUK KEMASAN KADALUARSA PADA PERLINDUNGAN HUKUM BAGI KONSUMEN - Fitriah, Fitriah (Solusi, 2020)
This study aims to examine the legal protection of consumers against expired packaged food products. Consumer is every person or business entity that is either a legal entity or not that can use a product and / or service that is obtained through the buying and selling process, gift or gift, and the product can be consumed directly. Consumers can not be separated from the rights and obligations of producers. In this case the manufacturer is the party that produces the product. In fact there are still many business actors who deliberately sell their food products that have expired, and this is not realized by consumers, because consumers just take it for granted without paying attention. And this is very detrimental to the rights of consumers and can endanger their health and safety. The Consumer Protection Act No. 8 of 1999 aims to protect consumers against their rights as well as the prohibition of producers in producing dangerous products. The government is authorized and responsible for regulating and overseeing the production, processing, distribution of food and beverages.